Intense intra‐3d luminescence and waveguide properties of single Co‐doped ZnO nanowires. Issue 10 (1st July 2013) - Geburt, Sebastian; Röder, Robert; Kaiser, Uwe; Chen, Limei; Chu, Manh‐Hung; Segura‐Ruiz, Jaime; Martínez‐Criado, Gema; Heimbrodt, Wolfram; Ronning, Carsten
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Successful doping of ZnO nanowires with the transition metal cobalt was achieved by ion implantation. Excellent optical activation of the incorporated Co ions was observed from nanowire ensembles after annealing. Efficient excitation of the Co ions occurs either by near resonant absorption or by energy transfer from the ZnO host. The excited Co ions decay radiatively with a lifetime of 8 ns. Intense and homogeneous Co2+ intra‐3d luminescence was observed from single nanowires with different Co concentrations in the range of 0.02– 4 at% and at various excitation powers. Spatially resolved measurements allowed the characterization of the waveguide properties of single doped nanowires. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)